ANALISIS OPTIMASI USAHATANI KELOMPOK TANI PAJALE (PADI, JAGUNG DAN KEDELE) DI KABUPATEN MINAHASA SELATAN - Christian M. Sumampouw; Prof.Dr.Ir. Robert Molenaar,MS.; Dr.Ir. Dedie Tooy, MSi. (COCOS, 2017)
ABSTRACT Geographically, South Minahasa district lies between 1 ° 17'18.22 "north latitude and 124 ° 54'48.84" east longitude, with a total area is 1188.67 km2, or approximately 8% of the total area of North Sulawesi (15.069.00 km2 ), with the coast in the north and south and the high plains, where irrigated rice fields provide an abundant harvest. Nature and the weather in this area is suitable for agricultural. At almost all districts  various agricultural crops can grow. Rice cultivation is mostly irrigated, in addition there is still also a rainfed. Planting is done two to three timesa year  and sometimes rotated withother food  crops. Food crops cultivated by the inhabitants consist of rice, corn, potatoes, and other food crops as well as various other horticultural crops. Besides Rice, South Minahasa also produces maize and cassava in relatively large quantities. Thus, the food crop farmers in South Minahasa can choose from various types of crops that can be cultivated in their agricultural lands. This study was conducted in August until September 2016 in South Minahasa regency. Required data were collected using survey methods, and analyzed with linear programming method using  solver application in Microsoft excel. Based on the research results, if the labor supply increased by 2 per family farmers and harvesting is done by machines  the farmer income per year increased from Rp 720 million, - to Rp 1.84 billion, - obtained from the cropping pattern of 15 hectares rice and 10 hectares corn for Musafir 4 farmer groups. the same goes for the Torout Jaya farmer groups, revenue per year increased from Rp 582 million, - to Rp 2.3241 billion, - which is obtained from the cropping pattern 17 hectares of rice and 20 hectares of soybeans.  Keywords : Optimization Farming, Linear Programming, Solver